Novel range overlap of three ursids in the Canadian subarctic - Douglas Andrew Clark; Ryan Brook; Chelsea Oliphant-Reskanski; Michel P. Laforge; Kiva Olson; Danielle Rivet (Arctic Science, 2019)
We describe for the first time in the peer-reviewed literature observations of American black bear (Ursus americanus Pallas, 1780), grizzly bear (Ursus arctos Linnaeus, 1758), and polar bear (Ursus maritimus Phipps, 1774) at the same locations. Using remote cameras we documented 401 bear-visits of all three species at three camps in Wapusk National Park, Canada, from 2011–2017. These observations add to a growing body of evidence that grizzlies are undergoing a substantial range increase in northern Canada and the timing of our observations suggests denning locally. Polar and grizzly bears are of conservation concern regionally and internationally, so from the literature we assessed the potential effects on conservation efforts from interactions between these three species. In aggregate, those effects are likely to be positive for grizzlies and weakly negative for black and polar bears; further research is needed. Range overlap of these three species in this dynamic ecotonal region should not be viewed as a threat to any of them, but rather as an ecological response to environmental change that needs to be better understood.